Vibration response and failure modes analysis of the temporary support structure under blasting excavation of tunnels. (June 2022) - Guan, Xiaoming; Yang, Ning; Zhang, Wenjun; Li, Minggeng; Liu, Zeliang; Wang, Xiaohui; Zhang, Sulei
Highlights: The dynamic response laws of the central diaphragm structure after the explosion were studied according to the field monitoring. The damage characteristics of the central diaphragm near the blasting source were investigated and the four stages of the failure evolution were summarized. The vibration response and the failure modes of the central diaphragm structure under the condition of different charge quantities and blasting distances were simulated. The relation function containing the blasting tensile stress index was obtained through dimensional analysis. Abstract: The blasting impact poses a serious threat to the safety of temporary support structures in tunnel blasting construction, such as a temporary middle wall. Thus, this study investigated and explored these problems. First, the dynamic response results of the temporary middle wall after the explosion were studied according to the field monitoring data. Subsequently, the damage characteristics of the temporary middle wall near the blasting source were investigated on field, and the development stages of the failure evolution were summarized. Furthermore, combined with the explicit finite element software LS-DYNA, the fluid–solid coupling algorithm was used to simulate the vibration response and the failure modes of the temporary middle wall under the condition of different charge weight and blasting distances. According to the field investigation, the closest blasting holes away from the temporary middle wall had a much more significant impact on its damage than other holes. The failure reason of the sprayed concrete of the supporting structure is caused by the excess high peak tension or compression stress. The failure process of supporting structure can be divided into four development stages with the reduced distance away from the blasting source: the appearance of the cracks, the cracks interconnect to form large X-shaped cracks, structural bending-shear coupling failure, and instability failure. The displacement values of the steel arch in the temporary middle wall continuously exceed 7 cm, 20 cm, 28 cm, and 34 cm, respectively, corresponding to the above four failure stages. The relation function containing the blasting tensile stress (BTS) parameter is obtained through dimensional analysis, which can be directly used to design and the damage evaluated of temporary support structures subjected to blasting at close range.